Universal sensors for identifying use-dependent intracellular allosteric modulators of G protein coupled receptors - Farmer, James (2024)
G protein-coupled receptors (GPCRs) represent the largest family of cell surface receptors targeted by therapeutics. Their diverse signalling capabilities lead to involvement in a wide range of physiological and disease responses. The vast majority of molecules currently available to target GPCRs are designed to act at the binding site (the orthosteric site) for endogenous ligands, either promoting receptor signalling as agonists, or inhibiting as antagonists. However, a continuing challenge within GPCR drug discovery is to develop compounds with sufficient selectivity across closely related targets, and more nuanced mechanisms of action than classical agonism or antagonism. Ultimately these may offer both improved therapeutic efficacy, and better minimise the occurrence of on- and off-target side effects.